Incidence of Acute Appendicitis on Histopathology (Medical Forum Monthly, 2024)
Objectives: To evaluate the incidence of appendectomy due to acute appendicitis and its conformation by histopathology so that the true positive and false positive procedures can be estimated.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the Department of General Surgery, Nishtar Hospital Multan from February 2016 to January 2017.Materials and Methods: A total two hundred and forty five (245) patients with clinical diagnosis of acute appendicitis were included in the study. Data was analyzed on computer software SPSS version 23. Mean and standard deviation ware calculated for numerical variables, frequency and percentages were calculated for categorical variables. P value ≤ 0.05 was considered as significant.Results: The main outcome variable of our study was Positive Appendectomy in all the patients of appendectomy due acute appendicitis. It was seen that out of 245 (100%) subjects, 75.1% (n=184) were found true positive appendectomy and 24.9% (n=61) were found false positive appendectomy.Alternatively, it was also observed that out of 245 (100%) patients, 24.9% (n=61) were negative appendectomy and 75.1% (n=184) were positive appendectomy.When patients were grouped in different age categories it was seen that majority of the patients 77.1% (n=189) were of age 20 to 40 years. And only 22.9% (n=56) were of 41 to 60 years of age.Conclusion: Surgeons should keep in mind the all possibilities of parasitic infestations mimicking acute appendicitis and confirmation of all clinical diagnosis with histological findings in our setting justifies routine histopathological examination of appendices.